Pengaruh Media Wordwall Dan Media Interaktif Power Point Terhadap Keterampilan Menulis Teks Anekdot Siswa Kelas X SMAN 1 Kalanganyar Tahun Ajaran 2023/2024 - Lianti, Lianti; Hilaliyah, Tatu; Iriyansah, M. Rinzat (Jurnal Ilmiah Wahana Pendidikan, 2025)
The skill of writing anecdotal texts is often one of the writing skills that is difficult, not mastered and not in demand by students. As a result of this, many students are unfocused and unable to write good anecdotal texts. The aim of this research is to describe the influence of Wordwall media, PowerPoint interactive media and the differences in the influence of Wordwall media and PowerPoint interactive media on the anecdotal text writing skills of class X students at SMAN 1 Kalanganyar. This research uses an experimental method with a quantitative approach and a pretest-posttest control group design. The sampling technique in this research used a simple random sampling technique, and class X-5 was selected as the experimental class and class X-1 as the control class. The data collection technique for this research comes from the results of anecdotal text writing tests in the form of pretest and posttest, with assessment instruments containing content, organization, vocabulary, language use and mechanics. The results of this research show the influence of wordwall media with an average pretest score of 58.9 and an average posttest score of 81.5 with a point difference of 22.6. And the influence of interactive powerpoint media with pretest results showing an average score of 52.9 and posttest with an average of 72.8 and a point difference of 19.9. So it is concluded that wordwall media is superior to powerpoint interactive media in improving skills write student anecdote texts. For this reason, learning skills to write anecdotal texts will be better by using wordwall media.